Enhanced dispersion and electronic performance of single-walled carbon nanotube thin films without surfactant: A comprehensive study of various treatment processes. (November 2015) - Azoz, Seyla; Gilbertson, Leanne M.; Hashmi, Sara M.; Han, Patrick; Sterbinsky, George E.; Kanaan, Stacy A.; Zimmerman, Julie B.; Pfefferle, Lisa D.
Abstract: A method for enhancing electronic performance of single-walled carbon nanotube (SWCNT) thin films through enhanced dispersion of SWCNTs in aqueous solutions is presented. The best dispersion enhancement is obtained by covalent attachment of urea to the acid functionalized SWCNTs. Dispersion properties of urea treatment are compared to conventional chemical and physical treatment techniques, such as surfactants. The treatment type and time significantly influence SWCNT surface functionalization, which determines the dispersion effectiveness as described by the SWCNT aggregate size, morphology and stability. The findings suggest that urea-SWCNTs, as compared to surfactant dispersed-SWCNTs, resulted in the most effective dispersion method among chemical treatments, yielding the smallest monodispersed aggregates with the most rod-like morphology that were stable over the greatest range in pH. Thin films prepared with SWCNT samples were evaluated for their transparency and resistance, two metrics that are important for electronics device applications. The urea-SWCNT films exhibited superior optoelectrical properties compared to SWCNT films prepared with conventional chemicals as well as surfactants. This indicates a correlation between degree of dispersibility and optoelectrical properties.